Synthesis of novel polymer quaternary ammonium salt derived from glucose as a phase transfer catalyst - IHSAN ALRUBAIE; AHMED THAMER SALIM; MOHAUMAN MOHAMMAD MAJEED; ALI JABBAR RADHI (Smujo International, 2022)
Abstract. Alrubaie I, Salim AT, Majeed MM, Radhi AJ. 2022. Synthesis of novel polymer quaternary ammonium salt derived from glucose as a phase transfer catalyst. Nusantara Bioscience 14: 25-33. Some new polymers containing quaternary ammonium salts based-carbohydrate starting from methyl-4,6-O-benzylidene-glucopyranoside have been prepared. The ammonium groups are connected to the glucose structure in various positions (2 and 3). Our synthesis used methyl-4,6-O-benzylidene-?-D-glucopyranoside through nucleophilic reagents to produce the main intermediates. The monomer glucose-quaternary ammonium salts are immobilized on the polyvinyl azide to give the final structure of the Polymer-Supported quaternary ammonium salts. In certain new kinds of phase transfer catalysts, the effectiveness of the polymer glucose-quaternary ammonium salts was tested in the Williamson etherification. Ether synthesis is a typical example of using a phase transfer catalyst. The reactions were performed in a liquid-liquid two-phase system, applying a mixture of toluene and a 50% solution of aqueous sodium hydroxide in the presence of a 20 mg/mmol catalyst (compound 9). Compared to other derivatives, the reaction of 4-nitrophenol with dibromoethylene gives the highest yields. On the other hand, compound 9 with the C16 chain gives high activity in the phase transfer catalyst.